PENGARUH PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KETERAMPILAN PSIKOMOTORIK DAN HASIL BELAJAR PRAKTEK PROYEK WORK - Nadya, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research was studying deeply about the effect of project based learning in improving psychomotor skills and the learning outcomes to. This research were analyzed by using quantitative analysis. The population in this research was the students of XII PM 1 SMK Negeri 8 Pontianak The research evealed that the independent variable and the dependent variable were effecting one another. The value of the effect was 0.960, it was closed to 1. This number indicated that the project based learning variable gave major impact to psychomotor skills and the learning outcomes of project work prctice. The percentage of project based learning variable toward the psychomotor skills and the learning outcomes of project work practice was 92.1% while the remaining 7.9% was influenced by other variable which were not included in the variables of this research. The regression coefficient from X was 1.238 which revealed the positive effect of X variable toward Y1. Every addition of single unit to X variable and another dependent variable remained the same then itu would add 1.238 to Y1 variable. Regression coefficient from X was 1.024 which revealed that X vriable gave positive impact to Y2. Every single X variable addition and another dependent variable remained the same then it would add 1.024 to Y2 variable.Based on partial analysis (T-Test), it was indentified that t-calculatin > than t-table for psychomotor skills variable and the learning outcomes of project work practice. It indicates that Ho hypothesis was rejected and Ha was accepted Keywords : PBL, Psychomotor Skills and Learning Outcomes,